2020
DOI: 10.3390/w12102897
|View full text |Cite
|
Sign up to set email alerts
|

General Assessment of the Operational Utility of National Water Model Reservoir Inflows for the Bureau of Reclamation Facilities

Abstract: This work investigates the utility of the National Oceanic and Atmospheric Administration’s National Water Model (NWM) for water management operations by assessing the total inflow into a select number of reservoirs across the Central and Western U.S. Total inflow is generally an unmeasured quantity, though critically important for anticipating both floods and shortages in supply over a short-term (hourly) to sub-seasonal (monthly) time horizon. The NWM offers such information at over 5000 reservoirs across th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Generally, the limitations of model‐based approaches in the calculation of flow values, as with the case of the NWM, come from limited infiltration quantification abilities, especially noted in semiarid regions (Lahmers, et al, 2021), lack of subsurface tile drainage representation (Valayamkunnath et al, 2022), channel routing schemes (Frame et al, 2021), or general simplified hydrologic process representations, and forcing errors (Viterbo, Mahoney, et al, 2020; Viterbo, Read, et al, 2020). Additionally, it must be noted that in the current version of NWM data (v2.1) only about 5000 reservoirs across the United States are represented in the model in terms of simplified input–output rules, and the model efficiency in representing real conditions is largely unknown (Viterbo, Mahoney, et al, 2020; Viterbo, Read, et al, 2020). The impact of reservoir operations on high and low flow peaks is critical; however, with the currently available data, it cannot be assessed in a consistent, distributed manner either by the use of the NWM v2.1 data set or by observed USGS data.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Generally, the limitations of model‐based approaches in the calculation of flow values, as with the case of the NWM, come from limited infiltration quantification abilities, especially noted in semiarid regions (Lahmers, et al, 2021), lack of subsurface tile drainage representation (Valayamkunnath et al, 2022), channel routing schemes (Frame et al, 2021), or general simplified hydrologic process representations, and forcing errors (Viterbo, Mahoney, et al, 2020; Viterbo, Read, et al, 2020). Additionally, it must be noted that in the current version of NWM data (v2.1) only about 5000 reservoirs across the United States are represented in the model in terms of simplified input–output rules, and the model efficiency in representing real conditions is largely unknown (Viterbo, Mahoney, et al, 2020; Viterbo, Read, et al, 2020). The impact of reservoir operations on high and low flow peaks is critical; however, with the currently available data, it cannot be assessed in a consistent, distributed manner either by the use of the NWM v2.1 data set or by observed USGS data.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To date a number of published works have documented various performance aspects of the NWM. These works have analyzed several aspects of the skill of reservoir inflow forecast performance (Viterbo, Read, et al., 2020) and snow model performance (Garousi‐Nejad & Tarboton, 2022). Viterbo, Mahoney, et al.…”
Section: Ongoing Developmentmentioning
confidence: 99%
“…Some applications have also focused on using the the historic data to study issues such as seasonal low flow in the Colorado River basin (Hansen et al, 2019), the one-way surface-groundwater flux in the Northern High Plains Aquifer during extreme flow events (Jachens et al, 2020), operational flood map generation (Johnson et al, 2019); cross section representation (Brackins et al, 2021); and reservoir inflow performance (Viterbo et al, 2020). In the latter, the authors specifically found that NWM inflows in snow-driven basins outperformed those in raindriven and that basin area, upstream management, and calibrated basin area influenced the ability to reproduce daily reservoir inflows.…”
Section: Introductionmentioning
confidence: 99%